2020
DOI: 10.1002/pds.5173
|View full text |Cite
|
Sign up to set email alerts
|

Influence of statin‐potency on the risk of kidney disease – A nationwide cohort study using laboratory data

Abstract: PurposeTo estimate the risk of kidney disease in high‐potency statin users compared to those treated with low‐potency statins without history of kidney disease at statin initiation, linking the Swedish national healthcare registers and laboratory data.MethodsIncident users of statins, ≥40 years of age, with estimated Glomerular Filtration Rate (eGFR) >60 ml/min/1.73 m2 and no diagnosis of kidney disease at treatment initiation were identified between 2006 and 2007 and then followed for 2‐years. The outcome … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 46 publications
(52 reference statements)
0
1
0
Order By: Relevance
“…There is evidence that statins might also have nephroprotective effects and slow the progression of CKD (a slower decline in glomerular filtration rate among statin users) [ 78 ]. However, other studies found that high-dose statin therapy, as compared with low-dose therapy, was associated with an increased risk of kidney disease [ 79 ]. The anti-inflammatory and antioxidant effects of statins can be beneficial in patients with autoimmune diseases [ 80 ].…”
Section: Discussionmentioning
confidence: 99%
“…There is evidence that statins might also have nephroprotective effects and slow the progression of CKD (a slower decline in glomerular filtration rate among statin users) [ 78 ]. However, other studies found that high-dose statin therapy, as compared with low-dose therapy, was associated with an increased risk of kidney disease [ 79 ]. The anti-inflammatory and antioxidant effects of statins can be beneficial in patients with autoimmune diseases [ 80 ].…”
Section: Discussionmentioning
confidence: 99%